National human rights action planning - Chalabi, Azadeh (Oxford : Oxford University Press, 2018)
Advancing a new general theory of human rights planning and drawing on a content analysis of nine core human rights treaties and a cross-case study of national human rights action plans (NHRAPs) of 53 countries, this volume sets out how these plans should be best developed, implemented, monitored, and how to maximize their effectiveness.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 31, 2018).
Keywords: Human rights; Human rights -- Cross-cultural studies; National human rights institutions; Human rights monitoring; Politics and Government; Politics & government